2014
DOI: 10.1111/1756-185x.12279
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of immunoglobulin G4‐related aortitis in cases with aortic resection and their clinical characteristics compared to other aortitises

Abstract: In patients with chronic aortic inflammation, 7% had IgG4-related aortitis. This disease may be more common in older male patients than in other demographic groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 15 publications
0
14
0
3
Order By: Relevance
“…Yoo et al . identified three cases of IgG4‐related aortitis and showed that these patients were older and more likely to be male than those with other forms of LVV . Another study suggested that elevated serum IgG4, male gender, higher calcium content of the aortic wall, and multifocal organ involvement might distinguish IgG4‐related periaortitis from idiopathic periaortitis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yoo et al . identified three cases of IgG4‐related aortitis and showed that these patients were older and more likely to be male than those with other forms of LVV . Another study suggested that elevated serum IgG4, male gender, higher calcium content of the aortic wall, and multifocal organ involvement might distinguish IgG4‐related periaortitis from idiopathic periaortitis .…”
Section: Discussionmentioning
confidence: 99%
“…31 Yoo et al identified three cases of IgG4-related aortitis and showed that these patients were older and more likely to be male than those with other forms of LVV. 37 Another study suggested that elevated serum IgG4, male gender, higher calcium content of the aortic wall, and multifocal organ involvement might distinguish IgG4-related periaortitis from idiopathic periaortitis. 10 The results of our study were consistent with previous reports regarding the overall male predominance of CP, but no significant difference in sex predisposition between IgG4-related and non-IgG4related cases was observed.…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34][35][36][37][38][39] Lindsay and colleagues presented a case with periaortitis. 32) An abdominal CT scan revealed periaortic soft tissue surrounding the abdominal aorta from below the level of the renal arteries.…”
Section: Aortic Lesionsmentioning
confidence: 99%
“…33,34) Patients with IgG4-related aortitis were older than those with Takayasu's arteritis or Behcet's aortitis, and were more likely to be male than those with Takayasu's arteritis. 35) Aneurysmal changes can also occur. Nuñez Fernández and colleagues described a case of aneurysmal dilatation of the ascending aorta.…”
Section: Aortic Lesionsmentioning
confidence: 99%
“…IgG4-related diseases are newly recognized systemic disorders, and they can affect a variety of different organs. IgG4-related inflammatory changes can also cause different morphological changes in the aorta [1][2][3][4][5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%